Economic Consequences of Covid-19 Pandemic: An Analysis of Exchange Rate Behaviour - Sethi, Maheswar; Dash, Sakti Ranjan; Kumar Swain, Rabindra; Das, Seema (Organizations and Markets in Emerging Economies, 2021)
This paper examines the effect of Covid-19 on currency exchange rate behaviour by taking a sample of 37 countries over a period from 4th January 2020 to 30th April 2021. Three variables, such as daily confirmed cases, daily deaths, and the world pandemic uncertainty index (WPUI), are taken as the measure of Covid-19. By applying fixed-effect regression, the study documents that the exchange rate behaves positively to the Covid-19 outbreak, particularly to daily confirmed cases and daily deaths, which implies that the value of other currencies against the US dollar has been depreciated. However, the impact of WPUI is insignificant. On studying the time-varying impact of the pandemic, the study reveals that the Covid-19 has an asymmetric impact on exchange rate over different time frames. Further, it is observed that though daily confirmed cases and daily deaths show a uniform effect, WPUI puts an asymmetric effect on the exchange rate owing to the nature of economies.